دور تحليل مؤشرات جودة السيولة وفق المعيار المحاسبي الدولي رقم 7 في تحسين الأداء المالي دراسة حالة مؤسسة سانياك عين الكبيرة سطيف : The role of analyzing liquidity quality indicators according to International Accounting Standard No 7 in improving financial performance, A case study of the saniak enterprise at Ain Kebira Setif. - مسعود بويباون (Journal of North African Economies, 2025)
This study aims to shed light on the role of financial ratios derived from the liquidity quality index, in improving the financial performance of the institution, through preparing and analyzing the treasury liquidity table in accordance with Accounting Standard No 07. It was found that the cash coverage ratio is good in the institution, which means that the internal cash flow from operating activities covers cash flows for investment, the necessary cash flow coverage ratio are considered weak, so the institution must take appropriate measures to address These imbalances allow for the aim of improving its financial performance in the future. Keywords: International Accounting Standard No 7, liquidity quality index, cash coverage ratio, necessary cash flow coverage ratio, financial performance.